Solid-state laminated high-voltage battery and manufacturing process

By using block positive and negative electrodes, solid electrolyte separators and double-sided nickel-plated PTC designs in lithium batteries, combined with stamping process to create pole blocks, the problems of complex and poor safety of existing lithium batteries are solved, and the structure is simplified and Improved safety.

CN119495908APending Publication Date: 2025-02-21SHENZHEN XINZHENG ENERGY ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311035821.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing lithium battery manufacturing process has problems such as complex structure, long manufacturing cycle, complex production process and poor safety.

Method used

The solid-state stacked high-voltage battery design includes block positive and negative electrodes, solid electrolyte separators and double-sided nickel-plated PTCs, and the pole blocks are manufactured through stamping processes, simplifying the process flow and improving safety.

Benefits of technology

The battery structure is simplified, safety is improved, production cycles are shortened, and multiple complex process steps are eliminated.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495908A_ABST
    Figure CN119495908A_ABST
Patent Text Reader

Abstract

The solid-state laminated high-voltage battery structurally comprises a shell, two battery cell modules, a conductive elastic sheet, a PTC (Positive Temperature Coefficient), an anti-explosion valve and a positive electrode cap, and a negative electrode plate is fixed at the bottom of the shell; the two battery cell modules, the conductive elastic sheet, the PTC and the explosion-proof valve are sequentially arranged in the shell from bottom to top, and the double-sided nickel-plated PTC is arranged between the two battery cell modules; each battery cell module comprises a negative electrode block, an electrolyte diaphragm and a positive electrode block which are sequentially distributed from bottom to top; and the anode cap is integrally welded with the open top of the shell. The positive electrode and the negative electrode are both of a blocky structure and are manufactured through a stamping process, a grade piece production process is replaced, coating, slitting, rolling, piece making, winding and liquid injection processes are omitted, a solid electrolyte diaphragm is arranged between the positive electrode and the negative electrode, meanwhile, a double-sided nickel-plated PTC is placed between battery cell modules, all the components are stacked to form a whole, the battery structure is simplified, and the cost is reduced. The manufacturing process is simplified, and the safety is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and more specifically to a solid-state laminated high-voltage battery and a manufacturing process. Background Art

[0002] Lithium batteries are a type of battery that uses lithium metal or lithium alloy as positive / negative electrode materials and non-aqueous electrolyte solutions. The structure of lithium batteries includes positive and negative electrodes, separators, negative electrodes, organic electrolytes and battery casings. The current lithium battery manufacturing process usually includes the following steps: 1) Preparation of positive and negative electrode materials (ingredients): manufacture positive electrode materials and negative electrode materials, where the positive electrode material is usually a mixture of lithium compounds (such as lithium cobalt oxide, ternary, lithium iron phosphate, etc.) and conductive agents, solvents, and binders (such as carbon black), and the negative electrode material is usually a mixture of graphite and conductive agents; 2) Mixing and coating: Mix the positive and negative electrode materials with the binder to form an electrode slurry, and then apply the electrode slurry to the mixture. 1) Coating the material on copper foil (positive electrode) and aluminum foil (negative electrode) to form electrode sheets; 2) Winding: Alternately stack the positive and negative electrode sheets with the separator (usually a polymer film) and wind them into an electrode group through a winding mechanism; 3) Liquid injection and packaging: Place the electrode group in the battery case and inject the electrolyte (usually an organic solution containing lithium salts), then seal the battery case to ensure that the electrolyte does not leak; 4) Molding and testing: Molding the sealed battery case, usually by pressing or heating, and then testing the molded battery. It can be seen that the current lithium batteries have complex structures, long manufacturing cycles, complex production processes and poor safety.

[0003] Therefore, providing a simplified solid-state laminated high-voltage battery and manufacturing process is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0004] In view of this, the present invention provides a solid-state laminated high-voltage battery and a manufacturing process to simplify the structure and process and improve safety.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] A solid-state laminated high-voltage battery, comprising:

[0007] A shell, wherein a negative electrode plate is fixed to the bottom of the shell;

[0008] A plurality of battery modules, conductive springs, PTCs and explosion-proof valves, wherein the plurality of battery modules, conductive springs, PTCs and explosion-proof valves are sequentially placed inside the housing from bottom to top, and a double-sided nickel-plated PTC is placed between two adjacent battery modules; each battery module comprises a negative electrode block, an electrolyte diaphragm and a positive electrode block sequentially distributed from bottom to top;

[0009] A positive electrode cap is welded to the open top of the shell as a whole.

[0010] By adopting the above scheme, the beneficial effects of the present invention are:

[0011] Both the positive and negative electrodes are block structures, and a solid electrolyte membrane is set between the two. At the same time, a double-sided nickel-plated PTC is placed between the battery cell modules. The various components are stacked to form a whole, which simplifies the battery structure and improves safety.

[0012] Furthermore, the negative electrode block is made of lithium-based / copper-based active material.

[0013] Furthermore, the electrolyte membrane is made of lithium zirconium oxychloride.

[0014] Furthermore, the positive electrode block is made of aluminum-based high-nickel active material.

[0015] Furthermore, the shell is made of plastic or metal.

[0016] Furthermore, the negative electrode plate is a conductive nickel-plated steel sheet.

[0017] The manufacturing process according to the solid-state laminated high-voltage battery as described above includes the following steps: first, the negative electrode block, electrolyte membrane, positive electrode block, double-sided nickel-plated PTC, negative electrode block, electrolyte membrane and positive electrode block are assembled into the interior of the shell in order from bottom to top, and so on, and the action is repeated according to the required voltage. Finally, the conductive spring, PTC and explosion-proof valve are assembled on the positive electrode block near the top of the shell in order from bottom to top, and the positive electrode cap is covered on the open top of the shell and ultrasonically welded.

[0018] By adopting the above scheme, the beneficial effects of the present invention are:

[0019] The negative electrode block and the positive electrode block are manufactured by a stamping process, which replaces the graded sheet production process, eliminating the coating, striping, rolling, sheet making, winding and liquid injection processes. During assembly, only the various parts need to be stacked together in order, simplifying the lithium battery manufacturing process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0021] Figure 1 The accompanying drawing is a schematic structural diagram of a solid-state laminated high-voltage battery in Example 1 provided by the present invention;

[0022] Figure 2 The accompanying drawing is a schematic structural diagram of a solid-state laminated high-voltage battery in Example 2 provided by the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1:

[0025] like Figure 1 As shown, the embodiment of the present invention discloses a solid-state laminated high-voltage battery with a voltage of 7.4v, including a shell 1, two battery modules, a conductive spring 5, a PTC 6, an explosion-proof valve 7 and a positive electrode cap 8. A negative electrode plate is fixed at the bottom of the shell 1; the two battery modules, the conductive spring 5, the PTC 6 and the explosion-proof valve 7 are placed inside the shell 1 from bottom to top, and a double-sided nickel-plated PTC 9 is placed between the two battery modules; each battery module includes a negative electrode block 2, an electrolyte diaphragm 3 and a positive electrode block 4 distributed from bottom to top; the positive electrode cap 8 is welded to the open top of the shell 1 as a whole. The positive and negative electrodes of the present invention are both block structures, and a solid electrolyte diaphragm 3 is arranged between the two. At the same time, a double-sided nickel-plated PTC 9 is placed between the battery modules. The various components are stacked to form a whole, which simplifies the battery structure and improves safety.

[0026] Specifically, the negative electrode block 2 is a lithium-based / copper-based active material. In this embodiment, the negative electrode substrate is foamed lithium or foamed copper; the negative electrode active material is graphite; the negative electrode binder is 1% PVDF or SBR or UHMWPE; and the negative electrode conductive agent is acetylene black or CNT or conductive graphite.

[0027] Specifically, the electrolyte membrane 3 is made of lithium zirconium oxychloride, which is synthesized from hydrated lithium hydroxide, lithium chloride and zirconium chloride, and has a relatively low cost.

[0028] Specifically, the positive electrode block 4 is an aluminum-based high-nickel active material. In this embodiment, the positive electrode substrate is foamed aluminum, which is low in cost and light in weight; the positive electrode active material is a high-nickel ternary material; the positive electrode adhesive is 1% PVDF or UHMWPE; and the positive electrode conductive agent is acetylene black or CNT or conductive graphite.

[0029] Specifically, the housing 1 is made of plastic or metal. In this embodiment, the plastic material is PE, PVC or PP, and the metal material is steel or aluminum.

[0030] Specifically, the negative electrode plate is a conductive nickel-plated steel sheet.

[0031] The embodiment of the present invention also discloses a manufacturing process according to the above solid-state laminated high-voltage battery, including the following steps: first, assemble the negative electrode block 2, electrolyte membrane 3, positive electrode block 4, double-sided nickel-plated PTC 9, negative electrode block 2, electrolyte membrane 3, positive electrode block 4, conductive spring 5, PTC 6 and explosion-proof valve 7 into the shell 1 (shell 1 wraps them up) in order from bottom to top, and finally cover the positive electrode cap 8 on the open top of the shell 1 and form a seal by ultrasonic welding. The negative electrode block 2 and positive electrode block 4 of the present invention are manufactured by stamping process, replacing the stage production process, eliminating the coating, striping, rolling, sheeting, winding and injection processes, and only need to stack the parts together in order during assembly, which simplifies the lithium battery manufacturing process and shortens the production cycle.

[0032] Specifically, when the housing 1 is produced, a conductive nickel-plated steel sheet is placed in a mold of an injection molding machine and thermoformed.

[0033] Specifically, the manufacturing of positive electrode block 4 and negative electrode block 2 is generally done through the steps of weighing raw materials → passing through magnets → vacuum stirring → vibration filling → extrusion molding. The following is the wet manufacturing process of the electrode block (positive electrode block 4 and negative electrode block 2 are referred to as electrode blocks for short): 1) Weigh the amount of each raw material according to the formula, use designated tools to add the raw materials and pour them into the mixing tank for stirring. The designated tools are added to prevent cross contamination between materials. The main material must be passed through a magnet, and the raw materials must be screened for impurities to filter out magnetic impurities such as iron. The mixing tank is vacuumed to about -80KPa. Long stirring time in the mixing tank will generate high temperature, causing the stirred slurry to agglomerate and oxidation reaction to occur. Therefore, it is necessary to add cooling water to the mixing tank during the stirring process to cool the slurry, so that the slurry is evenly stirred and the temperature of the slurry is maintained between 20-40 degrees. The temperature of the cooling water is generally between 12-18 degrees; 2) After the stirring is completed, the slurry is tested for viscosity, solid content, and particle size, and the process documents are followed. If it does not meet the requirements, continue stirring until the next process can be carried out after the test is qualified; 3) Use high The raw materials and the substrate are filled with high-frequency vibration equipment, which is referred to as vibration filling. Since the substrate is a foam structure metal with a large number of micropores, the stirred slurry is poured into the substrate for high-frequency vibration filling. After the filling is completed, the volume density is tested to see if it meets the design requirements. If not, the slurry is continued to be vibrated and filled until the test is qualified before the next process can be carried out; 4) The filled plate (after the substrate and slurry are filled, it is referred to as: plate) is placed in a special tray, and is placed in a vacuum -100pka, high temperature 85 degree environment with the tray for baking for 12-24 hours. The volume density and water content are tested to see if they meet the design requirements. If not, continue to bake until the test is qualified before the next process can be carried out; 5) The baked plate is placed in a stamping mold for stamping. The shape of the stamping is determined by the mold, and the thickness is determined by the stamping compression ratio. The stamping shape can be round, square, etc. After stamping, the thickness and volume density are measured to see if they meet the design requirements. If not, continue to adjust the compression ratio of the stamping equipment until the test is qualified before the next process can be carried out; 6) The qualified plate after stamping is referred to as the untested block.

[0034] Working principle of the present invention:

[0035] 1) Since the base materials of the positive electrode block 4 and the negative electrode block 2 are aluminum and copper, they cannot be directly connected (direct connection will cause electrochemical corrosion and lead to virtual connection), so nickel is needed to transition the potential difference of the metal material itself. The use of double-sided nickel-plated PTC9 can protect the consistency of the working current and charge and discharge current density of the battery cell, and can restore the overcurrent fuse. The double-sided nickel-plated PTC9 has a rated working current of 1A. When the battery cell charge and discharge exceeds the rated working current, the charge and discharge will be cut off. It can be restored after removing the load or waiting for the double-sided nickel-plated PTC9 to cool down;

[0036] 2) The electrolyte membrane 3 is solid. Compared with traditional liquid electrolytes, solid electrolytes have the following characteristics: High safety: solid electrolytes have higher chemical and thermal stability, and can effectively inhibit thermal runaway reactions inside the battery. Compared with liquid electrolytes, solid electrolytes are more stable under extreme conditions such as high temperature and external force impact, reducing the risk of thermal runaway of the battery; No leakage risk: solid electrolytes are in solid form and will not leak or overflow, avoiding battery leakage problems that may be caused by liquid electrolytes, which also means that solid-state batteries can be designed to be more compact and lightweight; Inhibit lithium metal dendrite growth: solid electrolytes can effectively inhibit the growth of lithium metal dendrites during charging and discharging, reducing the risk of short circuits and internal short circuits in lithium metal batteries, which is very important for improving battery safety and cycle life; Resistance to overcharge and overdischarge: solid electrolytes have higher electrochemical stability and can resist abnormal working conditions such as overcharge and overdischarge. This helps to reduce the energy loss and safety risks of the battery during the charging and discharging process; in addition, in the lithium battery test items, acupuncture and extrusion have no effect on the high-voltage battery of the present invention, because the present invention is a stack structure, not a winding structure, the positive electrode block, the electrolyte membrane, and the negative electrode block are all in three-dimensional form, and the outer shell is made of insulating plastic after the needle is inserted. The needle will not form an electronic circuit when it is inserted into the positive electrode block or the electrolyte membrane or the negative electrode block, and will not cause thermal runaway; the positive electrode block and the negative electrode block themselves are stamped and formed, so they are not afraid of destructive experiments such as extrusion; suppress the risk of thermal runaway: the solid electrolyte has high thermal stability and can effectively suppress the thermal runaway reaction inside the battery. Compared with liquid electrolytes, solid electrolytes are more stable under extreme conditions such as high temperature and external force impact, reducing the risk of thermal runaway of the battery; suppress external short circuit: the solid-state properties of the solid electrolyte can effectively prevent external substances from entering the battery, reducing the risk of external short circuit.

[0037] Embodiment 2:

[0038] like Figure 2 As shown, the embodiment of the present invention discloses a solid-state laminated high-voltage battery with a voltage of 11.1V, including a shell 1, three battery modules, a conductive spring 5, a PTC 6, an explosion-proof valve 7 and a positive electrode cap 8, and a negative electrode plate is fixed at the bottom of the shell 1; the three battery modules, the conductive spring 5, the PTC 6 and the explosion-proof valve 7 are placed inside the shell 1 from bottom to top, and a double-sided nickel-plated PTC 9 is placed between two adjacent battery modules; each battery module includes a negative electrode block 2, an electrolyte membrane 3 and a positive electrode block 4 distributed from bottom to top; the positive electrode cap 8 is welded to the open top of the shell 1 as a whole. The positive and negative electrodes of the present invention are both block structures, and a solid electrolyte membrane 3 is arranged between the two. At the same time, a double-sided nickel-plated PTC 9 is placed between the battery modules. The various components are stacked to form a whole, which simplifies the battery structure and improves safety.

[0039] Specifically, the negative electrode block 2 is a lithium-based / copper-based active material. In this embodiment, the negative electrode substrate is foamed lithium or foamed copper; the negative electrode active material is graphite; the negative electrode binder is 1% PVDF or SBR or UHMWPE; and the negative electrode conductive agent is acetylene black or CNT or conductive graphite.

[0040] Specifically, the electrolyte membrane 3 is made of lithium zirconium oxychloride, which is synthesized from hydrated lithium hydroxide, lithium chloride and zirconium chloride, and has a relatively low cost.

[0041] Specifically, the positive electrode block 4 is an aluminum-based high-nickel active material. In this embodiment, the positive electrode substrate is foamed aluminum, which is low in cost and light in weight; the positive electrode active material is a high-nickel ternary material; the positive electrode adhesive is 1% PVDF or UHMWPE; and the positive electrode conductive agent is acetylene black or CNT or conductive graphite.

[0042] Specifically, the housing 1 is made of plastic or metal. In this embodiment, the plastic material is PE, PVC or PP, and the metal material is steel or aluminum.

[0043] Specifically, the negative electrode plate is a conductive nickel-plated steel sheet.

[0044] The embodiment of the present invention also discloses a manufacturing process according to the above solid-state laminated high-voltage battery, including the following steps: first, assemble the negative electrode block 2, electrolyte membrane 3, positive electrode block 4, double-sided nickel-plated PTC9, negative electrode block 2, electrolyte membrane 3, positive electrode block 4, double-sided nickel-plated PTC9, negative electrode block 2, electrolyte membrane 3, positive electrode block 4, conductive spring 5, PTC6 and explosion-proof valve 7 into the shell 1 (shell 1 wraps them up), and finally cover the positive electrode cap 8 on the open top of the shell 1 and form a seal by ultrasonic welding. The negative electrode block 2 and the positive electrode block 4 of the present invention are manufactured by a stamping process, replacing the stage production process, eliminating the coating, striping, rolling, film making, winding and injection processes, and only need to stack the parts together in order during assembly, simplifying the lithium battery manufacturing process and shortening the production cycle.

[0045] Specifically, when the housing 1 is produced, a conductive nickel-plated steel sheet is placed in a mold of an injection molding machine and thermoformed.

[0046] Specifically, the manufacturing of positive electrode block 4 and negative electrode block 2 is generally done through the steps of weighing raw materials → passing through magnets → vacuum stirring → vibration filling → extrusion molding. The following is the wet manufacturing process of the electrode block (positive electrode block 4 and negative electrode block 2 are referred to as electrode blocks for short): 1) Weigh the amount of each raw material according to the formula, use designated tools to add the raw materials and pour them into the mixing tank for stirring. The designated tools are added to prevent cross contamination between materials. The main material must be passed through a magnet, and the raw materials must be screened for impurities to filter out magnetic impurities such as iron. The mixing tank is vacuumed to about -80KPa. Long stirring time in the mixing tank will generate high temperature, causing the stirred slurry to agglomerate and oxidation reaction to occur. Therefore, it is necessary to add cooling water to the mixing tank during the stirring process to cool the slurry, so that the slurry is evenly stirred and the temperature of the slurry is maintained between 20-40 degrees. The temperature of the cooling water is generally between 12-18 degrees; 2) After the stirring is completed, the slurry is tested for viscosity, solid content, and particle size, and the process documents are followed. If it does not meet the requirements, continue stirring until the next process can be carried out after the test is qualified; 3) Use high The raw materials and the substrate are filled with high-frequency vibration equipment, which is referred to as vibration filling. Since the substrate is a foam structure metal with a large number of micropores, the stirred slurry is poured into the substrate for high-frequency vibration filling. After the filling is completed, the volume density is tested to see if it meets the design requirements. If not, the slurry is continued to be vibrated and filled until the test is qualified before the next process can be carried out; 4) The filled plate (after the substrate and slurry are filled, it is referred to as: plate) is placed in a special tray, and is placed in a vacuum -100pka, high temperature 85 degree environment with the tray for baking for 12-24 hours. The volume density and water content are tested to see if they meet the design requirements. If not, continue to bake until the test is qualified before the next process can be carried out; 5) The baked plate is placed in a stamping die for stamping. The shape of the stamping is determined by the die, and the thickness is determined by the stamping compression ratio. The stamping shape can be round, square, etc. After stamping, the thickness and volume density are measured to see if they meet the design requirements. If not, continue to adjust the compression ratio of the stamping equipment until the test is qualified before the next process can be carried out; 6) The qualified plate after stamping is referred to as the pole block.

[0047] Working principle of the present invention:

[0048] 3) Since the base materials of the positive electrode block 4 and the negative electrode block 2 are aluminum and copper, they cannot be directly connected (direct connection will cause electrochemical corrosion and lead to virtual connection), so nickel is needed to transition the potential difference of the metal material itself. The use of double-sided nickel-plated PTC9 can protect the consistency of the working current and charge and discharge current density of the battery cell, and can restore the overcurrent fuse. The double-sided nickel-plated PTC9 has a rated working current of 1A. When the battery cell charge and discharge exceeds the rated working current, the charge and discharge will be cut off. It can be restored after removing the load or waiting for the double-sided nickel-plated PTC9 to cool down;

[0049] 4) The electrolyte membrane 3 is solid. Compared with traditional liquid electrolytes, solid electrolytes have the following characteristics: High safety: solid electrolytes have higher chemical and thermal stability, and can effectively inhibit thermal runaway reactions inside the battery. Compared with liquid electrolytes, solid electrolytes are more stable under extreme conditions such as high temperature and external force impact, reducing the risk of thermal runaway of the battery; No leakage risk: solid electrolytes are in solid form and will not leak or overflow, avoiding battery leakage problems that may be caused by liquid electrolytes, which also means that solid-state batteries can be designed to be more compact and lightweight; Inhibit the growth of lithium metal dendrites: solid electrolytes can effectively inhibit the growth of lithium metal dendrites during the charging and discharging process, reducing the risk of short circuits and internal short circuits in lithium metal batteries, which is very important for improving the safety and cycle life of the battery; Resistance to overcharge and overdischarge: solid electrolytes have higher electrochemical stability and can resist abnormal working conditions such as overcharge and overdischarge. This helps to reduce the energy loss and safety risks of the battery during the charging and discharging process; in addition, in the lithium battery test items, acupuncture and extrusion have no effect on the high-voltage battery of the present invention, because the present invention is a stack structure, not a winding structure, the positive electrode block, the electrolyte membrane, and the negative electrode block are all in three-dimensional form, and the outer shell is made of insulating plastic after the needle is inserted. The needle will not form an electronic circuit when it is inserted into the positive electrode block or the electrolyte membrane or the negative electrode block, and will not cause thermal runaway; the positive electrode block and the negative electrode block themselves are stamped and formed, so they are not afraid of destructive experiments such as extrusion; suppress the risk of thermal runaway: the solid electrolyte has high thermal stability and can effectively suppress the thermal runaway reaction inside the battery. Compared with liquid electrolytes, solid electrolytes are more stable under extreme conditions such as high temperature and external force impact, reducing the risk of thermal runaway of the battery; suppress external short circuit: the solid-state properties of the solid electrolyte can effectively prevent external substances from entering the battery, reducing the risk of external short circuit.

[0050] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0051] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A solid-state laminated high-voltage battery, characterized in that: include: A shell, wherein a negative electrode plate is fixed to the bottom of the shell; A plurality of battery modules, conductive springs, PTCs and explosion-proof valves, wherein the plurality of battery modules, conductive springs, PTCs and explosion-proof valves are sequentially placed inside the housing from bottom to top, and a double-sided nickel-plated PTC is placed between two adjacent battery modules; each battery module comprises a negative electrode block, an electrolyte diaphragm and a positive electrode block sequentially distributed from bottom to top; A positive electrode cap is welded to the open top of the shell as a whole.

2. A solid-state laminated high-voltage battery according to claim 1, characterized in that: The negative electrode block is made of lithium-based / copper-based active material.

3. A solid-state laminated high-voltage battery according to claim 1, characterized in that: The electrolyte membrane is made of lithium zirconium oxychloride.

4. A solid-state laminated high-voltage battery according to claim 1, characterized in that: The positive electrode block is made of aluminum-based high-nickel active material.

5. A solid-state laminated high-voltage battery according to claim 1, characterized in that: The shell is made of plastic or metal.

6. A solid-state laminated high-voltage battery according to claim 1, characterized in that: The negative electrode plate is a conductive nickel-plated steel sheet.

7. A manufacturing process for a solid-state laminated high-voltage battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: firstly, assembling the negative electrode block, electrolyte membrane, positive electrode block, double-sided nickel-plated PTC, negative electrode block, electrolyte membrane and positive electrode block into the shell in order from bottom to top, and repeating the operation according to the required voltage, and finally assembling the conductive spring, PTC and explosion-proof valve on the positive electrode block near the top of the shell in order from bottom to top, and closing the positive electrode cap on the open top of the shell by ultrasonic welding.